Hubungan health literacy dengan manajemen diri pada pasien chronic kidney disease yang menjalani hemodialisis - Ni Komang Emi Trisnawati; Dewa Putu Arwidiana; Ni Made Nopita Wati Wati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2025)
Background: Patients with CKD undergoing hemodialysis require good self-management skills to maintain quality of life and prevent complications. One factor that influences the success of self-management is the level of health literacy, namely the individual's ability to access, understand, and use health information. Purpose: To determine the relationship between health literacy and self-management in CKD patients undergoing hemodialysi. Method: A descriptive correlational design with a cross-sectional approach. The sample consisted of 112 CKD patients undergoing hemodialysis, selected using a purposive sampling technique. The instruments used included health literacy and self-management questionnaires. Data analysis was performed using the Rank Spearman correlation test. Results: There was a significant relationship between health literacy and self-management in CKD patients undergoing hemodialysis (p <0.05). Patients with high levels of health literacy tend to have better self-management skills. Conclusion: Health literacy plays an important role in improving the self-management skills of hemodialysis patients. Improving health literacy through appropriate education can be an effective strategy in supporting long-term care of CKD patients. Keyword: Chronic Kidney Disease; Health Literacy; Hemodialysi; Self-Management. Pendahuluan: Pasien dengan penyakit CKD yang menjalani hemodialisis memerlukan kemampuan manajemen diri yang baik untuk menjaga kualitas hidup dan mencegah komplikasi. Salah satu faktor yang memengaruhi keberhasilan manajemen diri adalah tingkat literasi kesehatan (health literacy), yaitu kemampuan individu dalam mengakses, memahami, dan menggunakan informasi kesehatan. Tujuan: Untuk mengetahui hubungan antara health literacy dengan manajemen diri pada pasien CKD yang menjalani hemodialisis. Metode: Desain deskriptif korelasional dengan pendekatan cross-sectional. Sampel terdiri dari 112 pasien CKD yang menjalani hemodialisis, dipilih dengan teknik purposive sampling. Instrumen yang digunakan meliputi kuesioner health literacy dan manajemen diri. Analisis data dilakukan menggunakan uji korelasi Rank Spearman. Hasil: Terdapat hubungan yang signifikan antara health literacy dengan manajemen diri pada pasien CKD yang menjalani hemodialisis (p <0.05). Pasien dengan tingkat literasi kesehatan yang tinggi cenderung memiliki kemampuan manajemen diri yang lebih baik. Simpulan: Health literacy berperan penting dalam meningkatkan kemampuan manajemen diri pasien hemodialisis. Peningkatan literasi kesehatan melalui edukasi yang tepat dapat menjadi strategi efektif dalam mendukung perawatan jangka panjang pasien CKD. Kata Kunci: Health Literacy; Hemodialis; Manajemen Diri; Penyakit Gagal Ginjal Kronik.